(untitled) (Damu Journal of Sport Sciences, 2025)
The aim of the research was to identify differences in the practice of recreational activities among female university students (practicing and non-practicing recreational sports activities), differences in psychological well-being among female university students (practicing and non-practicing recreational sports activities), differences in cultural sports awareness among female university students (practicing and non-practicing recreational sports activities), differences in cultural sports awareness among female university students (practicing and non-practicing recreational sports activities), as well as identifying the relationship between practicing recreational activities and psychological well-being among female university students (practicing and non-practicing recreational sports activities), and understanding the relationship between practicing recreational activities and cultural sports awareness among female university students (practicing and non-practicing recreational sports activities). The research sample included a number of female university students (practicing and non-practicing recreational sports activities) for the academic year 2024-2025, totaling (200) students, with (100) practicing students. For recreational sports activities, (200) female students who did not participate in recreational sports activities were included The study reached the following conclusions: -1 There were statistically significant differences between the average responses of the research sample of female university students (practicers and non-practicers of recreational sports activities), in favor of those who practiced recreational sports activities, in terms of (recreational activity objectives, recreational activity content, and overall scale). -2 There were no statistically significant differences between those who practiced and non-practicers of recreational sports activities, in terms of (recreational activity capabilities and preferred recreational activities). -3There were statistically significant differences in psychological well-being between female university students (practicers and non-practicers of recreational sports activities), in favor of those who practiced recreational sports activities, in terms of (positive self-esteem, physical health, and overall scale). -4 There were no differences between female university students (practicers and non-practicers of recreational sports activities) in terms of (social relationships and psychological happiness).